Reutilización de equipos de cómputo desactualizados con Linux Terminal Server Project en la Facultad de Ingeniería de Sistemas e Informática de la Universidad Nacional de San Martín - Sánchez Gárate, Silvia Karo (2013)
The undated getting computer equipment, it has made a big problem for the society in the environment because of it busies an unnecessary environment of work that could serve to the administrative or academic works, furthermore, it generates a partial lost of the National university of San Martín patrimony and it affects to the pollution of the soil, water and air, then, such technology unities send toxic chemistry elements that affect the health of the people. The nowadays investigation has as a topic Reuse of undated computer equipment with LTSP technology in the Faculty of Systems and Informatics Engineering of the National University of San Martín, that consists in a project such the aim is reduce the getting the undated computer equipment, prolonging its useful life and doing working at the maximum production, so, they come back to be use again as computer of desk and this can not be used used as a got computers. It was used (LTSP) Linux Technology Terminal Server Project as a tool that allows the reuse of undated computer equipment, whose get a low qualification and has little resources of hardware the same that are considered as fast customers or fool terminals (LTSP) it gives an easy operative system that is about Linux, getting lest costs of license and repairing; furthermore, gives an environment of work free of viruses